2010
DOI: 10.1056/nejmoa0908014
|View full text |Cite|
|
Sign up to set email alerts
|

Telaprevir for Previously Treated Chronic HCV Infection

Abstract: In HCV-infected patients in whom initial peginterferon alfa and ribavirin treatment failed, retreatment with telaprevir in combination with peginterferon alfa-2a and ribavirin was more effective than retreatment with peginterferon alfa-2a and ribavirin alone. (ClinicalTrials.gov number, NCT00420784.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
497
3
14

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 656 publications
(527 citation statements)
references
References 14 publications
13
497
3
14
Order By: Relevance
“…En effet, les nouvelles drogues ont une activité pangénotypique, il n'y a pas de résistance génotypique croisée entre les différentes classes d'antiviraux directs, et d'autres types de traitement sont en cours de développement. Ces autres antiviraux, tels que les inhibiteurs de la cyclophiline, les inhibiteurs d'entrée du virus dans les cellules, les ARN anti-sens, ainsi que la vaccinothérapie, permettront, dans les situations les plus difficiles, de dépasser un génotype 1), avec une réduction de 48 à 24 semaines de la durée du traitement chez la moitié des patients (ceux qui ont une réponse virologique rapide définie par l'absence de détection du virus après 4 semaines de traitement) [15][16][17][18][19][20]. La limite principale de ces traitements est celle des effets secondaires, en plus de ceux liés au traitement classique : effets cutanés (télaprévir) avec des rashs sévères dans 5 à 10 % des cas [21], et une anémie (télaprévir ou bocéprévir) [22].…”
Section: Revuesunclassified
“…En effet, les nouvelles drogues ont une activité pangénotypique, il n'y a pas de résistance génotypique croisée entre les différentes classes d'antiviraux directs, et d'autres types de traitement sont en cours de développement. Ces autres antiviraux, tels que les inhibiteurs de la cyclophiline, les inhibiteurs d'entrée du virus dans les cellules, les ARN anti-sens, ainsi que la vaccinothérapie, permettront, dans les situations les plus difficiles, de dépasser un génotype 1), avec une réduction de 48 à 24 semaines de la durée du traitement chez la moitié des patients (ceux qui ont une réponse virologique rapide définie par l'absence de détection du virus après 4 semaines de traitement) [15][16][17][18][19][20]. La limite principale de ces traitements est celle des effets secondaires, en plus de ceux liés au traitement classique : effets cutanés (télaprévir) avec des rashs sévères dans 5 à 10 % des cas [21], et une anémie (télaprévir ou bocéprévir) [22].…”
Section: Revuesunclassified
“…Five factors associated with achieving an SVR were: assignment to a boceprevir group; previous relapse versus nonresponse; low viral load at baseline; absence of cirrhosis; and >1 log 10 IU/mL decrease in HCV RNA levels at week 4 (18). telaprevir Phase 1 and phase 2 trials established efficacy in a daily dosage regimen of 750 mg three times a day of telaprevir in both treatment-naive and treatment-experienced patients (19)(20)(21)(22)(23)(24)(25). Because pegIFN and ribavirin are associated with many dose-and duration-limiting adverse events, phase 2 trials assessed whether telaprevir could be combined with pegIFN alone without coadministration of ribavirin.…”
Section: Efficacymentioning
confidence: 99%
“…In previous studies reported that when the Peg-IFN + RBV and TVR treatment compared to the standard therapy, the rate of SVR can significantly improve in the patients infected with HCV genotype 1 [6][7][8][9] Although the treatment success was increased in TVR added regimens when RBV removed the treatment with TVR, SVR rates was lower than the standard therapy [6,10].…”
Section: Discussionmentioning
confidence: 99%
“…Telaprevir (TVR) is an orally bioavailable drug for non-structural 3/4A HCV protease inhibition [5]. When TVR is combined with PegIFN plus RBV, sustained virologic response (SVR) rates are increased significantly in patients with treatment experience [6,7].…”
Section: Introductionmentioning
confidence: 99%